Pengaruh Struktur Kepemilikan, Ukuran Komite Audit dan Kualitas Audit Terhadap Luas Pengungkapan Kompensasi Manajemen Kunci di Laporan Keuangan [Effects of Ownership Structure and Audit Committee Size on the Disclosure of Executive Management Compensation in Financial Statements] - Kristiana Gabriela Astri Astasari; Yeterina Widi Nugrahanti (Universitas Pelita Harapan, 2015)
The purpose of this study is to investigate the effect of ownership structure and audit committee's size to the disclosure of executive management compensation in the Financial Statement. The research 's samples are 125 manufacturing companies that listed in Indonesia Stock Exchange in 2012. The results of this research show that managerial ownership and audit committee's size does not have a significant effect to the disclosure of executive management compensation in the Financial Statements. Besides that, institutional ownership has a negative significant effect to the disclosure of executive management compensation in the Financial Statements.